2011
DOI: 10.1016/j.rmed.2011.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary involvement in pleural tuberculosis: How often does it mean disease activity?

Abstract: The present study demonstrates that pulmonary involvement is quite common in pleural tuberculosis. This finding is mainly observed in high-resolution computed tomography and has important epidemiological implications, since patients with pleural tuberculosis are significant sources of infection and disease dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Approximately 60% of patients with pleural TB had concomitant lung parenchymal abnormalities, which was consistent with a previous report showing that more than 80% of patients with pleural TB had pulmonary parenchymal abnormalities [1315]. In addition, previous studies showed that patients with pleural TB often developed active pulmonary TB at a later time [23] and that a delay in anti-TB treatment of more than 14 days was associated with a worse clinical outcome after one year of follow-up in patients with neutrophil-predominant pleural TB [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Approximately 60% of patients with pleural TB had concomitant lung parenchymal abnormalities, which was consistent with a previous report showing that more than 80% of patients with pleural TB had pulmonary parenchymal abnormalities [1315]. In addition, previous studies showed that patients with pleural TB often developed active pulmonary TB at a later time [23] and that a delay in anti-TB treatment of more than 14 days was associated with a worse clinical outcome after one year of follow-up in patients with neutrophil-predominant pleural TB [24].…”
Section: Discussionsupporting
confidence: 91%
“…Lung parenchymal lesions were defined as pulmonary findings, such as micronodules, consolidation, and cavitation, that were compatible with pulmonary TB on initial chest computed tomography (CT) [1315]. For patients without an available chest CT, patchy or nodular shadows and cavitation that were observed on the initial chest X-ray and that improved after anti-TB treatment were considered to be parenchymal lesions [16].…”
Section: Methodsmentioning
confidence: 99%
“…We included pleural TB as a respiratory form of disease because of the high probability that a case reported as pleural also has pulmonary involvement (3638). …”
Section: Methodsmentioning
confidence: 99%
“…In another study, TB was the third leading cause of massive effusions, following malignancy and pneumonia [22]. In approximately 20% to 25% of patients with pleural effusions secondary to TB [21,23], coexisting parenchymal disease is visible on the chest radiograph. If chest CT scans are done, approximately 86% will have parenchymal abnormalities [24].…”
Section: Clinical Manifestationsmentioning
confidence: 99%